Rational swarm for global optimisation. (27th November 2012) - Li, Chenyang; Garcia, Alfredo
In this paper, we propose a novel bio–inspired multi–agent co–operative searching methodology for global optimisation, named Rational Swarm algorithm. It can be used both as a meta–heuristic guiding local search algorithm and as a high–level multi–agent co–operative searching strategy to coordinate multiple agents using meta–heuristics. In this work, the Rational Swarm methodology has been applied to a popular meta–heuristics Simulated Annealing (SA) and a pure local search algorithm Monotonic Sequential Basin Hopping (MSBH). Numerical experiments on various continuous optimisation problems show Rational Swarm can improve the performance of applied meta–heuristics/heuristics in terms of solution quality and robustness under the same computational budget. Convergence analysis gives the theoretical insights about why the proposed Rational Swarm Methodology will work.